Perspectivas e trajetória recente da área da cultura: Nota temática do catálogo de políticas públicas - Antônio de Pádua de Lima Brito (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This work analyzes the course of cultural policies in Brazil from a categorization of the area based on data that integrate the Catalog Platform of Public Policies. The starting point is a theoretical, conceptual, and historical analysis of the emergence of cultural policies broadly and their trajectory in the context of public policies, including at a global level. Then, with the creation of the Ministry of Culture (MinC) in 1985 as a milestone, the policies identified in the current version of the Catalog of Public Policies are classified and grouped into segments and subareas of culture in order to analytically delineate the trajectories verified and point out for possible trends, taking into account the recent ruptures resulting from the extinction of the MinC, which resulted in discontinuity, paralysis, and slowdown even of actions institutionalized at the constitutional level.
10419/284912
Keywords: I3; I31; 330; cultural policies; public policy; Catalog of Public Policies; knowledge management; planning